2016
DOI: 10.1007/s11695-016-2468-6
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Health-Related Quality of Life After Roux-en-Y Gastric Bypass Related to Weight Loss

Abstract: IntroductionEffect of bariatric surgery on health-related quality of life (HRQOL) varies greatly. This might be caused by the diversity in questionnaires used to assess HRQOL and the weight loss of the studied population. This study assesses the relationship between weight loss and HRQOL in primary Roux-en-Y gastric bypass (RYGB) patients by using an obesity-specific (impact of weight on quality of life-lite, IWQOL-lite) and a generic (RAND-36) questionnaire.MethodsHRQOL and weight parameters were assessed bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 23 publications
1
21
0
2
Order By: Relevance
“…All intensity levels of PA were higher 12-month post-surgery compared to pre-surgery, although not statistically significant, except for step counts. Great improvements in HRQoL after bariatric surgery, in line with our results, have been seen in several previous studies [ 12 , 13 , 23 ], with a peak improvement at 12-month post-surgery [ 33 ]. Contrary to previous studies on objectively measured PA after bariatric surgery [ 34 , 35 ], participants in the current study increased both MVPA and LPA at 12-month post-surgery.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All intensity levels of PA were higher 12-month post-surgery compared to pre-surgery, although not statistically significant, except for step counts. Great improvements in HRQoL after bariatric surgery, in line with our results, have been seen in several previous studies [ 12 , 13 , 23 ], with a peak improvement at 12-month post-surgery [ 33 ]. Contrary to previous studies on objectively measured PA after bariatric surgery [ 34 , 35 ], participants in the current study increased both MVPA and LPA at 12-month post-surgery.…”
Section: Discussionsupporting
confidence: 92%
“…Individuals suffering from obesity often show lower levels of HRQoL compared to the general normal weight population [ 10 ]. Weight loss has been associated with increases in HRQoL [ 11 ], especially rapid weight loss induced by bariatric surgery [ 12 14 ], where Roux-en-Y gastric bypass (RYGB) is the most commonly performed bariatric surgery procedure in Sweden [ 15 ]. Greatest improvements of HRQoL, induced by weight loss, are often seen on the physical part of the measurement scale, probably caused by the reduced physical complaints after losing weight, but the mental part has also been shown to improve [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three definitions of weight regain (regain > 10 kg, regain 5 BMI, and regain EWL 25) were related to the physical health component of the RAND-36, measuring HRQoL. Several studies have shown that HRQoL improves after bariatric surgery and that this improvement is related to the amount of weight lost [3, Table 5 Linear regression investigating the effect of weight regain, according to different definitions, on HRQoL [37][38][39]. They also show stronger associations with the physical health component than the mental health component [38,40].…”
Section: Discussionmentioning
confidence: 99%
“…The short form of impact of weight on quality of life (IWQOL-lite) is a 31-item questionnaire which assesses the impact of weight on quality of life with acceptable validity and reliability in patients with obesity (test-rest reliability r = 0.74–0.91; α = .85). It contains the five domains, i.e., physical function, self-esteem, sexual life, public distress, and work [ 31 , 32 ]. An overall score was used, as a principal component analysis extracted a single component with an eigenvalue > 1 ( λ = 3.21, R 2 = 64%).…”
Section: Methodsmentioning
confidence: 99%